Hypoxia inducible-factor 1 alpha regulates neutrophil recruitment during fungal-elicited granulomatous inflammation - da Silva-Ferreira, Sara; Duarte-Oliveira, Cláudio; Antunes, Daniela; Barbosa-Matos, Catarina; Mendes-Frias, Ana; Torrado, Egídio; Costa, Sandra; Silvestre, Ricardo; Cunha, Cristina; Carvalho, Agostinho (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic pulmonary aspergillosis (CPA) is a devastating disease with increasing prevalence worldwide. The characteristic granulomatous-like inflammation poses as the major setback to effective antifungal therapies by limiting drug access to fungi. These inflammatory lung structures are reported to be severely hypoxic; nevertheless, the underlying mechanisms whereby these processes contribute to fungal persistence remain largely unknown. Hypoxia-inducible factor 1 alpha (HIF-1α), besides being the major cellular response regulator to hypoxia, is a known central immune modulator. Here, we used a model of Aspergillus fumigatus airway infection in myeloid-restricted HIF-1α knock-out (mHif1α-/-) mice to replicate the complex structures resembling fungal granulomas and evaluate the contribution of HIF-1α to antifungal immunity and disease development. We found that fungal-elicited granulomas in mHif1α-/- mice had significantly smaller areas, along with extensive hyphal growth and increased lung fungal burden. This phenotype was associated with defective neutrophil recruitment and an increased neutrophil death, therefore highlighting a central role for HIF-1α-mediated regulation of neutrophil function in the pathogenesis of chronic fungal infection. These results hold the promise of an improved capacity to manage the progression of chronic fungal disease and open new avenues for additional therapeutic targets and niches of intervention.